2012
DOI: 10.5194/amt-5-2917-2012
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the long-term evolution of subtropical ozone profiles applying ground-based FTIR spectrometry

Abstract: Abstract. This study investigates the long-term evolution of subtropical ozone profile time series (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) obtained from ground-based FTIR (Fourier Transform InfraRed) spectrometry at the Izaña Observatory ozone super-site. Different ozone retrieval strategies are examined, analysing the influence of an additional temperature retrieval and different constraints. The theoretical assessment reveals that the FTIR system is able to resolve four indep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(107 citation statements)
references
References 29 publications
(31 reference statements)
17
90
0
Order By: Relevance
“…As a consequence, the absorption spectra contain some information on the vertical distribution of the absorbing trace gases. For example, in the case of O 3 four independent layers between the surface and about 35 km altitude García et al, 2012) and in the case of H 2 O three layers between the surface and the upper troposphere can be resolved.…”
Section: The Musica Ndacc/ftir Retrievalsmentioning
confidence: 99%
“…As a consequence, the absorption spectra contain some information on the vertical distribution of the absorbing trace gases. For example, in the case of O 3 four independent layers between the surface and about 35 km altitude García et al, 2012) and in the case of H 2 O three layers between the surface and the upper troposphere can be resolved.…”
Section: The Musica Ndacc/ftir Retrievalsmentioning
confidence: 99%
“…3, the errors in the spectroscopic line parameters could explain between 2 and 4 % of the FTS bias, according to our error estimation (see Appendix B). Indeed, experimental intercomparisons between FTS and Brewer observations carried out at IZO in the last years found that FTS systematically overestimates the Brewer O 3 TC amounts by ∼ 4 % Viatte et al, 2011;García et al, 2012b), which may be due to inconsistencies in the ultraviolet and infrared spectroscopic parameters. This implies that the IASI O 3 observations should have less bias with respect to the actual O 3 concentrations (less than 2 %).…”
Section: Comparison Between Iasi and Ground-based Fts Observationsmentioning
confidence: 99%
“…The good quality of these long-term ground-based FTS data sets has been extensively documented by theoretical and empirical validation studies (e.g. Schneider et al, 2006Sepúlveda et al, 2012;García et al, 2012b;Sepúlveda et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…An uncertainty of the instrumental line shape (ILS), which is a leading error source for the ground-based remote sensing of stratospheric trace gas profiles (e.g. García et al, 2012), is of lower importance for tropospheric water vapour retrievals. The reason is that most water vapour is situated at low altitudes.…”
Section: Estimation Of Uncertaintiesmentioning
confidence: 99%